Functional stability correlates with dynamic microbial networks in anammox process. (February 2023) - Ya, Tao; Huang, Yan; Wang, Kening; Wang, Jiaao; Liu, Junyu; Hai, Reti; Zhang, Tingting; Wang, Xiaohui
Graphical abstract: Highlights: Stochasticity predominated bacterial assembly during the whole study period. Overall networks became closer and more complex at the middle and end stages. Rare species presented a high diversity across five networks. Negative interactions between AnAOB and heterotrophs could keep functional stability. Chloroflexi and Proteobacteria alternately play important roles in networks. Abstract: Understanding the relationship between dynamic microbial networks and functional stability is critical for the stable operation of anammox systems. Here, by operating an anammox reactor under constant condition over 250 days, it was found that the relative abundance of Planctomycetota gradually decreased while Chloroflexi and Proteobacteria increased, with stochasticity predominating the bacterial assembly as the reactor operation. Network analysis revealed a successional dynamic pattern of microbial interaction despite stable performance. The variation of subnetworks indicated Chloroflexi and Proteobacteria alternately played important role in anammox microbial network, and the negative relationship between anammox bacteria and heterotrophs could achieve a balance to keep functional stability under long-term operation. Furthermore, the identified keystone species mainly belonged to heterotrophs that were critical in maintaining network structure and system function. The results of this study revealed clear changing patterns of microbial community and network succession, which could provide valuable reference for other stably operated bioreactors.